Theoretical and experimental study on the fiber optic displacement sensor with two receiving fibers - Harun, Sulaiman Wadi; Yang, H.Z.; Yasin, M.; Ahmad, Harith (John Wiley & Sons, 2010)
The intensity-modulation-based displacement sensor with two receiving fibers is theoretically, (aid experimentally studied. The mathematical model of the proposed sensor is developed and the simulated responses are obtained to be in a good agreement with the experimental results, Compared with the conventional sensor with only one receiving fiber, the proposed sensor has a better linearity range because it has a larger area to receive the reflected light from the target. However, the sensitivity of both sensors is almost similar. The proposed sensor has the maximum linearity ranges of 2.5 mu m and 0.9 mu m at the back and front slopes, respectively. The linearity ranges are improved by about 44% compared with the conventional sensor. (C) 2009 Wiley Periodicals, Inc. Microwave Opt Technol Lett 52: 373-375, 2010; Published online in Wiley InterScience (www.interscience.wiley.com). DOI 10.1002/mop.24900